2007
DOI: 10.1021/bm7004559
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Structure of the C-Terminal Domain of Dragline Spider Silk and the Role of Its Conserved Cysteine

Abstract: Dragline spider silk fibers have extraordinary attributes as biomaterials of superior strength and toughness. Previously we have shown that the conserved C-terminal domain of a dragline spider silk protein is necessary for directing oriented microfiber formation. Here we present for the first time a state-of-the-art model of the three-dimensional structure of this domain, and, by comparing several dragline proteins, identify its key evolutionarily conserved features. Further, using the baculovirus expression s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…We ( Huemmerich et al, 2004b) and subsequently others ( Huang et al, 2006, Ittah et al, 2007, Ittah et al, 2006, Lin et al, 2009and Stark et al, 2007 have shown the C-terminal NR domains to adopt a predominantly α-helical conformation in vitro. These domains have been postulated to form the outer layer of droplet-like structures observed in the spinning dope in vivo ( Jin and Kaplan, 2003, Lin et al, 2009and Vollrath and Knight, 1999.…”
Section: Introductionmentioning
confidence: 73%
“…We ( Huemmerich et al, 2004b) and subsequently others ( Huang et al, 2006, Ittah et al, 2007, Ittah et al, 2006, Lin et al, 2009and Stark et al, 2007 have shown the C-terminal NR domains to adopt a predominantly α-helical conformation in vitro. These domains have been postulated to form the outer layer of droplet-like structures observed in the spinning dope in vivo ( Jin and Kaplan, 2003, Lin et al, 2009and Vollrath and Knight, 1999.…”
Section: Introductionmentioning
confidence: 73%
“…100-200 amino acids and show-in contrast to the repetitive core-well defined secondary and tertiary structures in solution. 24,25 Due to conserved cysteine residues, these domains can establish intermolecular disulfide bonds and are thus able to stabilize dimers and multimers under oxidizing conditions. Therefore, these domains are thought to initiate and specify assembly of silk proteins.…”
Section: Gpggx/gpgqq [Iii] Ggx (X = a S Or Y) And [Iv]mentioning
confidence: 99%
“…[59] The C-terminus is also mainly a-helical with a highly conserved disulfide bridge, which is likely to be involved in the dimerisation of silk proteins. [60,61] Both termini are likely to be involved in the solubilisation and stabilisation of the repetitive regions in the solution state, in which it is stored prior to fibre formation. [28,60,61] The repetitive regions differ between the various types of silk but have similar individual modules that are present in more than one type of silk and that are typically repeated several times within a single silk molecule.…”
Section: Amyloids In Arthropodsmentioning
confidence: 99%